2001
DOI: 10.1046/j.1528-1157.2001.12200.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental Retardation in Pediatric Candidates for Epilepsy Surgery: The Role of Early Seizure Onset

Abstract: These results indicate that onset of intractable epilepsy within the first 24 months of life is a significant risk factor for MR, especially if seizures occur daily. The risk based on early age at seizure onset appeared independent of etiology and persisted within subgroups of patients with focal malformation of cortical development, tumor, or hippocampal sclerosis. Prospective studies will be important to clarify whether early surgical intervention may reduce the risk for subsequent MR in carefully selected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
66
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 29 publications
14
66
1
4
Order By: Relevance
“…Austin and colleagues (37) found that children with active epilepsy had lower scores on school progress and intellectual self-concept than children with inactive epilepsy. Intractable epilepsy in children with onset before age two has been associated with poor cognitive functioning (38). Moreover, in the sample of children with new-onset seizures, our finding that academic performance among those with recurrent seizures tended to decline over time is consistent with results from previous research (7,8,10,32), emphasizing the importance of identifying academic difficulties among children with seizures as early as possible so that interventions may be implemented that limit the progression of problems.…”
Section: Discussionsupporting
confidence: 89%
“…Austin and colleagues (37) found that children with active epilepsy had lower scores on school progress and intellectual self-concept than children with inactive epilepsy. Intractable epilepsy in children with onset before age two has been associated with poor cognitive functioning (38). Moreover, in the sample of children with new-onset seizures, our finding that academic performance among those with recurrent seizures tended to decline over time is consistent with results from previous research (7,8,10,32), emphasizing the importance of identifying academic difficulties among children with seizures as early as possible so that interventions may be implemented that limit the progression of problems.…”
Section: Discussionsupporting
confidence: 89%
“…In support of this view, intellectual outcome is particularly poor if seizures begin prior to the age of five [5,[13][14][15][16][17], with the poorest outcomes associated with seizure onset in the first year of life [11,18]. The effect of age at onset persists once factors such as seizure control [14,19], number of antiepileptic drugs (AEDs) [19], etiology [20], duration of epilepsy [14,19,21], and extent of pathology are controlled [22], implying that developmental processes have an independent effect on cognitive outcome. Some recent studies have explored the relationship between age at seizure onset and specific cognitive functions across childhood.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of intractable epilepsy before the age of 2 years, especially when seizures occur daily, has been reported to be a risk factor for subsequent mental retardation [37]. Moreover, a shorter duration of frequent seizures before surgery may lead to a better long-term cognitive outcome [38].…”
Section: Discussionmentioning
confidence: 99%